Near-fatal negative pressure pulmonary oedema successfully treated with venovenous extracorporeal membrane oxygenation performed in the hybrid emergency room. Issue 9 (9th September 2020) - Matsumura, Kazuki; Toyoda, Yukitoshi; Matsumoto, Shokei; Funabiki, Tomohiro
Abstract : We report a rare case of negative pressure pulmonary oedema (NPPE), a life-threatening complication of tracheal intubation. A 41-year-old obese man was admitted to a previous hospital for neck surgery. After extubation, he developed respiratory distress followed by haemoptysis and desaturation. The patient was reintubated and brought to our hospital where we introduced venovenous extracorporeal membrane oxygenation (ECMO) to prevent cardiac arrest, which is an unusual clinical course for NPPE. He returned to his routine without any sequelae. This is the first case report of NPPE successfully resolved with venovenous ECMO in the hybrid emergency room (hybrid ER), which is a resuscitation room equipped with interventional radiology features and a sliding CT scanner. Since the hybrid ER serves as a single move for patients where all necessary procedures are performed, it has the potential to lower the incidence of cannulation complications, beyond the delay in ECMO initiation.